Clinical and epidemiological profile of acute chagas disease in the state of Minas Gerais, Brazil - Pereira, Cláudia Marta Luiz; Azevedo, Ana Paula; Marinho, Sandra da Silva Barros; Prince, Karina Andrade de; Gonçalves, Jaqueline Teixeira Teles; Costa, Marina Ramos; Espírito Santo, Luçandra Ramos (Journal of Health Care, 2017)
Introduction: The state of Minas Gerais, Brazil, presents very significant numbers of Chagas endemic disÂease, and although attempts to control it show positive results, there are still a substantial number of cases in several regions of Minas Gerais. Objective: To know the clinical and epidemiological aspects of acute Chagas disease in the state of Minas Gerais. Methodology: This is a descriptive and documental study, with quantiÂtative approach, based on Minas Gerais. Data were collected in the Brazilian Ministry of Health's Notifiable Diseases Information System (SINAN), considering the number of cases reported in the period from 2001 to 2006. Notification forms were used when there was suspicion of one of the compulsory notification disÂeases, as well as Chagas disease acute investigation forms. The main variables obtained were: health macroreÂgion, area of residence, mode of infection and evolution of the case. Results: Between the years of 2001 and 2006, 84 cases of acute Chagas disease were recorded in Minas Gerais. The region with the highest number of cases was the western region, followed by the northern. The majority of individuals were urban residents. The main mode of transmission was by vector, and most cases evolved to remission of clinical manifestations. Conclusion: Knowing the clinical and epidemiological aspects of Chagas disease and spreading the findings will allow the elaboration and implementation of strategies to fight the disease chronification.
Keywords: Chagas disease; Epidemiology; Health information systems; Notification of diseases